2004
DOI: 10.1002/jppr2004344290
|View full text |Cite
|
Sign up to set email alerts
|

Public Health—Recognising the Role of Australian Pharmacists

Abstract: This article describes the philosophy of public health as it relates to the work of pharmacists. Individual patient care provided by pharmacists when supplying medicines is placed within a public health framework and existing public health roles performed by pharmacists are presented. Newly emerging public health roles and public health opportunities for pharmacists in developing countries are outlined. Education relevant to the practice of public health is discussed both as a component of pharmacy training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…[8][9][10] Research findings have confirmed the positive contribution and the potential of the professional performance of pharmacists in providing public-health initiatives. 11 Interestingly, a broadening of this role has been suggested for better involvement in health promotion and prevention activities.…”
Section: Innovations In Pharmacymentioning
confidence: 87%
See 1 more Smart Citation
“…[8][9][10] Research findings have confirmed the positive contribution and the potential of the professional performance of pharmacists in providing public-health initiatives. 11 Interestingly, a broadening of this role has been suggested for better involvement in health promotion and prevention activities.…”
Section: Innovations In Pharmacymentioning
confidence: 87%
“…10,12 It was designed with 4 parts; Part 1 encompasses demographic data (gender, age, educational levels, monthly income levels, and disease status). Part 2: The use of community pharmacy (number of visits, reason/s of visiting a pharmacy, the main influence to select a pharmacy, and the first person to consult) in which a multiple choices answer was used.…”
Section: Study Toolmentioning
confidence: 99%
“…Health promotion plans focus on community based interventions and partnerships to maintain wellness and to help modify individual behaviours such as unhealthy lifestyles [3]. Community pharmacies are being recognised as highly suitable health promotion settings due to the high volume of the population that use their services [4]. In Australia, community pharmacies are the most accessible with over 90% of the population visiting at least once each year [5].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] This health promotion service is one aspect of the broad public health role of community pharmacy. 33 Given that healthy behaviour change requires multiple strategies, it is also worth considering the evaluation benchmarks for community pharmacy health promotion programs. 24 While smoking cessation programs conducted in community pharmacy have been evaluated against behavioural change, this may not be appropriate for all health behaviours.…”
Section: Health Promotionmentioning
confidence: 99%